PEMBELAJARAN MATERI EKOSISTEM DENGAN JIGSAW MELALUI HYPERMEDIA DAN MODUL DITINJAU DARI KEMAMPUAN MEMORI DAN INTERAKSI SOSIAL SISWA - Tri Lukitaningsih (Florea : Jurnal Biologi dan Pembelajarannya, 2014)
The objectives of the research were to know: 1) the effect of Jigsaw learning through Hypermedia and module toward  student’s achievement; 2) the effect of high and low memory ability toward  student’s achievement; 3) the effect of high and low social interaction toward  student’s achievement; 4) interaction between learning media and memory ability toward student’s achievement; 5) interaction between learning media and social interaction toward the student’s achievement; 6) interaction between memory ability and student social interaction toward the student’s achievement; 7) interaction between learning media and memory ability and student social interaction toward the student’s achievement. The research sample was determined by random cluster sampling technique that consists of two classes. Data collection techniques for achievement tests and memory skills, social interaction questionnaire for. Anova test hypotheses using 2x2x2 factorial design with the help of software Minitab 15.1.2. Based on the research were concluded : 1)  There was an effect of with hypermedia and module toward the student’s achievement. 2) There was no effect of memory ability to ward student’s achievement. 3) There was an effect of social interaction  toward student’s achievement. 4) There was no interaction between learning media and student’s memory ability toward student’s achievement. 5) There was no interaction between learning media  and social interaction toward student’s achievement. 6) There was no interactoin memory ability and social interaction  toward student’s achievement. 7) There was no interaction memory ability, social interaction, and learning media  toward student’s achievement .